Mergers and Acquisitions (M&A) of Municipal Owned Entities (MOEs) in South Africa: the case of Johannesburg City Parks and Zoo - Iroanya, R. O.; NJingolo, B. (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
Mergers and acquisitions are one way to make none performing enterprises productive and profitable. The City of Johannesburg Municipality (CoJ) has gone through a process of merging some of its municipal owned enterprises (MOEs) in recent years. Taking the case of the merger of the Johannesburg City Parks and Johannesburg Zoo to form a new company called Johannesburg City Park and Zoo, this paper draws from secondary sources such as municipal documents and data from interviews with different Johannesburg City Park and Zoo staff. The findings point to various problems which the merger has created for the Johannesburg City Park and Zoo which have negatively impacted on service delivery functions. The findings further indicate that the problems created by the merger are related to poor articulation of merger process; organisational fit; inadequate management of merger process; political imperativeness; low staff morale and satisfaction; and insufficient funding of merger process. These findings are consistent with theoretical exegesis in extant literature on mergers and acquisitions. The paper concludes with recommendations aimed at strengthening policy, strategies, and capacities. These are deemed necessary if the Johannesburg City Park and Zoo is to achieve its intended objectives.
Journal article, Published in International Conference on Public Administration and Development Alternatives (IPADA), The 2nd Annual Conference on ‛‛ The Independence of African States in the Age of Globalisation”, July 26-28, 2017
Keywords: Mergers and Acquisitions; City of Johannesburg; Municipal Owned Entities; Johannesburg City Park; Zoo; Consolidation and merger of corporations -- South Africa -- Gauteng; Local government -- South Africa -- Gauteng